2020
DOI: 10.1177/2632463620978044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adoption of Directly Measured Low-Density Lipoprotein-Cholesterol (LDL-C) on Targets of Lipid Control and Its Comparison With Friedewald Formula-Calculated LDL Cholesterol in People With Type-2 Diabetes Mellitus

Abstract: Objectives: The accurate and precise measurement of low-density lipoprotein-cholesterol (LDL-C) is important in the assessment of atherosclerotic cardiovascular disease risk (ASCVD) in people with diabetes mellitus. This study aimed at comparing directly measured LDL-C with Friedewald formula (FF)-calculated LDL-C (c-LDL-C) in people with type-2 diabetes. Methods: Fasting lipid profiles of 1905 people with type-2 diabetes, whose LDL-C was estimated by direct LDL assay, were chosen for the study. In the same gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Lin's concordance coefficient quantifies the robustness of a relationship between two measures by determining the deviation from the standard deviation, thus also accounting for systematic variations between methods. 18 Passing-Bablok regression showed that calculated LDL-C systematically underestimated LDL-C concentrations relative to measured LDL-C. Our results are in line with those of Jagesh 20 and Lee. 21 However, this finding is not agreement with reports from a study conducted by Ephraim et al in a Ghanaian population 22 and Boshtam et al in an Iranian population.…”
Section: Discussionsupporting
confidence: 90%
“…Lin's concordance coefficient quantifies the robustness of a relationship between two measures by determining the deviation from the standard deviation, thus also accounting for systematic variations between methods. 18 Passing-Bablok regression showed that calculated LDL-C systematically underestimated LDL-C concentrations relative to measured LDL-C. Our results are in line with those of Jagesh 20 and Lee. 21 However, this finding is not agreement with reports from a study conducted by Ephraim et al in a Ghanaian population 22 and Boshtam et al in an Iranian population.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were confirmed by Sathiyakumar et al who found that at TG concentrations of >4.5mmol/L, the Martin-Hopkins formula had a mean absolute deviation difference of 0.3, while the Friedewald formula had the lowest accuracy [ 31 ]. Jagesh et al also demonstrated that the Martin-Hopkins formula achieved a better precision at higher TG concentrations compared to the Friedewald formula [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The used Roche assay, which has its own bias compared to the reference method, cannot be assumed to represent “true LDL-C”. However, homogeneous assays for measuring LDL-C are routinely used and recommended by the NCEP [ 35 ] and their performance is within specifications by NCEP ATP III [ 32 ]. Also, our database was not linked to clinical data, therefore, we were unable to assess the effect of medical conditions or medications on lipid profile effect, as this was a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation